Geographia Polonica Vol. 81 No. 1 (2008) - Rączkowska, Zofia (1953– ). Ed.; Starkel, Leszek (1931– ). Ed. (IGiPZ PAN, 2008)
133 pp. ; 24 cm
Keywords: high-mountain relief; permafrost; glaciers; geomorphology; Canada; Alps; Carpathians; Sudety Mountains; Tatra Mountains; Bohemian Massif

Współczesne przekształcanie stoków w Tatrach Zachodnich – na przykładzie ścieżek turystycznych i fragmentów stoków bez oddziaływania antropogenicznego = Contemporary transformation of slopes in the Western Tatras - as exemplified by fragments with tourist footpaths or - Fidelus, Joanna (IGiPZ PAN, 2013)
24 cm
Keywords: slopes; man and environment; touristic movement; high mountains; West Tatra Mountains; Poland

Przegląd Geograficzny T. 74 z. 1 (2002) (IGiPZ PAN, 2002)
24 cm
Keywords: geographers; geographical studies; landscape architecture; geomorphology; anthropogenic changes of relief; snow cover; glaciers; Spitsbergen; Tatra Mountains; Ślęża Massif; Poland

Przyczynek do morfologji szaty śnieżnej = A contribution to the morphology of the snow-cover - Ormicki, Wiktor Rudolf (1898–1941) (nakł. Księgarni Geograficznej "Orbis", 1929)
14 pp. ; 25 cm
Przegląd Geograficzny, t. 9, r. 1929 p. 183-196
Summ. eng.
Keywords: snow cover

Przegląd Geograficzny T. 78 z. 3 (2006) (IGiPZ PAN, 2006)
24 cm
Keywords: structural geomorphology; land use; morphogenetic processes; anthropopression; tors morphology; geoecological catena; high mountains landscape; heat waves; mammals; Tatra Mountains; Sudety Mountains; Stołowe Mountains

Synoptyczne uwarunkowania intensywnych opadów śniegu w wybranych regionach Europy = Synoptic conditions underpinning intensive snowfalls in selected regions of Europe - Tomczyk, Arkadiusz Marek; Bednorz, Ewa (IGiPZ PAN, 2014)
The aim of the work described here has been to determine synoptic situations associated with intensive snowfalls in selected regions of Europe. Specifi cally, an analysis was carried out for three stations representing regions with different climatic conditions in winter. Synoptic conditions were characterized on the basis of atmospheric pressure at sea level, the height of the 500 hPa isobaric area and air temperature at the 850 hPa isobaric level. Typical features of synoptic situations leading to intensive snowfalls in Belgrade are negative SLP anomalies and a lowering height of the 500 hPa isobaric area over SouthernEurope, as indicating the presence of a low-pressure system. Heavy snowfalls in Suwałki, Poland, are in turn associated with the occurence of a low-pressure system centred on the south-eastern Baltic Sea. Finally, the occasional snowstorms characterising Ubachsberg in The Netherlands are associated with extensive low-pressure troughs that bring in humid and cold air masses from the north and north-west.
24 cm
Keywords: Europe; snow cover; circulation; synoptic conditions

Variability of selected extreme meteorological events in Poland - Łupikasza, Ewa; Bielec-Bąkowska, Zuzanna; Falarz, Małgorzata (IGiPZ PAN, 2009)
The principal aim of this paper is to analyze the trends of the multi-annual course of the selected characteristics of extreme precipitation, snow cover and atmospheric thunderstorms in the second half of the twentieth century in Poland. The results of these investigations show that in Poland it is only possible to determine a weak decreasing trend of extreme precipitation events in the S and especially in the SW part of the country. In northern Poland, opposite, although similarly weak, trends have also been observed. It is assumed that the most essential features of long-term changeability of extreme precipitation include a higher than average number of days with extremely high precipitation during the 1960s and 1970s, a distinctly lower frequency of such days during the 1950s, 1980s and in the first half of the1990s. In Poland it is possible to distinguish four broad homogenous areas in terms of the long-term changes in the occurrence of extreme precipitation events. There is considerable regional differentiation when it comes to the occurrence of thunderstorms in Poland, and their long-term changeability does not show any clear trends. Only three stations have determined a weak increase in the number of thunderstorms during the last 120 years. In some stations, an increase in the number of days with thunderstorms during the winter seasons was also observed. There were no significant trends in extreme snow cover in Poland. The periods that contained large and small areas of extreme snow cover thickness occurred alternately. Since the winter season 1987/88, the area of extremely thin snow cover has remained at a relatively high level.
24 cm
Keywords: extreme precipitation; thunderstorm; extreme snow cover; trends; Poland

Charakterystyka zasilania roztopowego w dorzeczu Warty na obszarzeNiziny Wielkopolskiej jako głównej składowej fal wezbraniowych = Characteristics of meltwater nourishment as the chief component of peakhigh-water events in the Wielkopolska Lowland part of the Warta Basin - Major, Maciej (IGiPZ PAN, 2012)
164 pp ; 24 cm
Keywords: meltwater nourishment; peak high-water events; snow cover; Warta basin; Wielkopolska Lowland

Badania fizyczno-geograficzne otoczenia stacji naukowo-badawczej Instytutu Geografii PAN w Szymbarku. T. 1 / - Dauksza, L.; Gil, Eugeniusz; Kotarba, Adam (1938– ); Kramarz, K.; Niemirowska, J.; Słupik, January; Starkel, Leszek (1931– ). Red. (IGiPZ PAN, 1970)
72 pp., [6] k. tabl. : il. ; 21 cm
Summary in English.
Bibliogr. p. 70
Keywords: physical geography; hydrology; snow cover; Szymbark

Mapa śniegowo-turystyczna z dn. 17 stycznia 1935 r. - Państwowy Instytut Meteorologiczny (Warszawa) (Wydawnictwo Państwowego Instytutu Meteorologicznego, 1935)
Skala [1:2 000 000]
1 mapa ; 50x45 cm, na ark. 60x50 cm
Tyt. z mapy
Pod mapą objaśnienia i wykaz rodzajów śniegu
Keywords: weather; snow cover; climatic maps; tourist maps; Poland

Zakłady przemysłowe wschodniej części aglomeracji krakowskiej jako źródło zanieczyszczenia pokrywy śnieżnej = Industrial plants in the eastern part of the Kraków agglomeration as a source of snow-cover pollution - Stachnik, Łukasz; Plenzler, Joanna; Żelazny, Mirosław (1962– ) (IGiPZ PAN, 2010)
24 cm
Keywords: snow cover pollution; chemical properties of snow; Cracow agglomeration; environment pollution; industrial plants

Narciarskia mapa śniegowa Ligi Popierania Turystyki - Kołodziejczyk, Stanisław. Oprac.; Niedenthal, Władysław. Oprac.; Wojtyński, Piotr. Oprac.; Państwowy Instytut Meteorologiczny (Warszawa); Towarzystwo Krzewienia Narciarstwa (Państwowy Instytut Meteorologiczny, 1935)
Skala [1:1 100 000]
Skala [1:4 300 000]
2 mapy na 1 ark. : kolor ; na ark. 48x63 cm
Tyt. z mapy
Pod mapą objaśnienia, wykaz rodzajów śniegu i wykaz posterunków pomiarów meteorologicznych
Keywords: outline maps; climatic maps; snow cover; Poland; Carpathians

Szorstkość pokrycia terenu jako źródło błędu metody SfM zastosowanej do rekonstrukcji zasięgu pokrywy śnieżnej = Terrain roughness as a source of error with the SfM method applied to the reconstruction of snow cover extent - Szafert, Damian. Autor; Miziński, Bartłomiej. Autor; Niedzielski, Tomasz. Autor (IGiPZ PAN, 2020)
A comparison between errors associated with snow-cover reconstruction performed by processing aerial imagery acquired by a visible-light camera mounted on board unmanned aerial vehicles, one the one hand; and average terrain roughness, on the other, revealed a dependent relationship between these variables. A stronger correlation is noted for two of the studied test areas (Polana Izerska and Krobica, both located in SW Poland), as opposed to the remaining site (Drożyna, SW Poland). In particular, correlations are noticeable where the analysis is performed in moving windows. It is typical for terrain where depth of snow cover is reconstructed with severe errors to reveal a high degree of roughness caused by single trees, clumps of trees or buildings. Ambiguous results are obtained for the Drożyna research field. While the character of the dependent relationship there seems consistent with results for the remaining sites, the strength is low. The lower values for the correlation coefficient were driven by observations for which errors were found to be high while values for the Topographic Ruggedness Index were at the same time low. This effect can be explained by reference to the specific nature of the area reconstructed, which is much transformed by human activity. It proves difficult to reconstruct the depth of snow cover on roads properly, as these are either partially cleared or snow or characterised by its loss in the course of melting. Low thickness of snow cover is thus found to be a constrained when it comes to the generation of accurate reconstructions of the depth of snow cover. This is in fact a finding in agreement with what has been reported by other authors.
24 cm
Keywords: extent of snow cover; Izerskie Mountains; Structure-from-Motion; roughness of land cover; unmanned aerial vehicle; geoinformatics

Związki pomiędzy pokrywą śnieżną a roślinnością na przykładzie grądów Białowieskiego Parku Narodowego = Relationships between snow cover and vegetation on example of oak-linden-hornbeam communities in the Białowieża National Park - Żarnowiecki, Grzegorz (IGiPZ PAN, 2008)
215 pp. : ill. ; 24 cm
Bibliogr. p.164-172
Summ. eng.
Keywords: forest ecology; snow cover; vegetation; oak-linden-hornbeam communities; Białowieża Forest; Białowieża National Park

Rzut oka na budowę geologiczną Tatrów i wzniesień od nich równoodległych : (z ryciną) - Zejszner, Ludwik (1805–1871). Autor ([s.n.], 1842)
40 s., [1] k. tabl. złoż. ; 21 cm
Przedr.: Biblioteka Warszawska, 1842, t. 1. (Nr. t. na podstawie BNPol online)
Estr. XIX t. 5, s. 282
Keywords: geology; Tatra Mountains

Z badań fizyczno-geograficznych w Tatrach = Physical geography study in the Tatra Mountains - Kotarba, Adam (1938– ). Red. (IGiPZ PAN, 1993)
81 pp., [5] k. tabl. : il. ; 24 cm
Summary in English.
Bibliogr.
Keywords: physical geography; Tatra Mountains

Die Hohe Tatra in den Central-Karpaten : eine geographische Skizze Verfasst auf Grundlage einer Bereisung - Kořistka, Karel František Edvard (1825–1906). Autor (Justus Perthes, 1864)
[4], 36 pages, [4] board cards: pictures; 28 cm
Mit einer Terrain-Karte, vier Ansichten in Farbendruck und einem Holzschnitt
OBV online
Keywords: geography; High Tatra Mountains

Kierunki polskich zastosowań ekologii krajobrazu w gospodarowaniu przestrzenią po 1982 r. = Polish application of landscape ecology in spatial management post-1982 - Kistowski, Mariusz (1963– ). Autor (IGiPZ PAN, 2019)
Landscape ecology and related sub-disciplines like geoecology and comprehensive physical geography are among the most applied of the geographical sciences. Comprehensive diagnosis, evaluation, planning and forecasting of human-environment interactions, as applied to spatial management or physical development, is the main direction in which ecological and landscape knowledge is seen to find application. In the light of that, the research presented here sought to present directions of application of landscape ecology among Polish researchers, in the years 1983-2017. The presentation was in the context of scientific research, with the most important monographs thematically convergent with these directions indicated. In the light of the expert and research achievements to date and the human-resources potential, prospects for the development of the sub-discipline were then outlined. Diagnostic and planning-related environmental studies of a mandatory nature, as well as environmental impact assessments and optional diagnostic studies were the kinds found to have been performed most frequently (accounting for 57% of the total). In turn, among the 35 detailed types of studies identified, the kinds produced most frequently involved thematic maps (mainly of a sozological nature), eco-physiographic studies and environmental impact reports (together accounting for 1/3 of all expert opinions). Expert opinions were most often commissioned by public administration (in 3/4 of all cases), be this local (in 1/3 of cases), regional or central. Expert opinions were most often produced for Commune Offices (26.7%) or the Offices of the Marshals at regional level (10%), or else for Ministries (mainly the Ministry of the Environment), or for industrial or infrastructural enterprises. The greatest numbers of expert opinions originated at the Gdańsk, Warsaw, Poznań, Opole, Łódź and Lublin centres. Landscape ecologists from individual centres specialise in selected directions of application, as is the case for Gdańsk (environmental impact assessments and GIS databases); Warsaw (diagnostic environmental studies); Lublin (studies of the optional type), and Kielce (obligatory planning--related studies). Within the six basic groups of studies – of which four are divided into two subgroups – there are several dozen examples of specific topics of expertise and a similar number of monograph titles presented. Changes in Polish legislation on science and higher education, as introduced in 2018, ay affect the organisation of institutions and research processes. Landscape ecologists will find themselves in two main areas (the social sciences as well as the pure and natural sciences) and disciplines (socio-economic geography and spatial management, as well as earth and environmental sciences), and some will also be found in technical and engineering sciences (environmental engineering, urban planning and architecture). Consequences of this might be either negative or positive, as the development might either activate interdisciplinary contacts or reduce opportunities for cooperation. At the same time, the state rules for assessing applications relating to scientific advancement or applying for funds for research projects still treat participation in the implementation of commercial projects marginally. Among the criteria for assessing the activity of scientific entities (and constituting the basis for their financing), the commercialisation of research in the form of application of scientific work confirmed by enterprises or public administration is also limited. This leaves the fate of Polish landscape ecology as hard to predict unambiguously, though, given the interdisciplinarity and desired directions of research resulting from the challenges of civilisation – the likelihood is that it will remain at the current level, or even develop further.
24 cm
Keywords: landscape ecology; geoecology; comprehensive physical geography; application studies

Problems and possibilities of lichenometric dating in Polish mountains - Kędzia, Stanisław (IGiPZ PAN, 2013)
24 cm
Keywords: Rhizocarpon; lichenometry; Tatra Mountains; Karkonosze Mountains

Tatry od północy - Zwoliński, Tadeusz (1893–1955). Rys. (Wydawnictwo Ligi Popierania Turystyki, 1936)
Not drawn to scale
1 view : lithogr., col. ; 64x73 cm
Keywords: Tatra Mountains views

Tatry Polskie : mapa środkowej części Tatr w podziałce 1:37 500 - Zwoliński, Tadeusz (1893–1955). Oprac. (Nakład i własność Księgarni L.[eonarda] Zwolińskiego, 1932)
Wyd. 7 popr. i uzup.
Scale 1:37 500
1 map : col. ; 82x54 cm, folded in cover 21x13 cm
Cover Title
Prime meridian Ferro
Keywords: tourist maps; Tatra Mountains

Tatry podczas epoki lodowej = The Tatra Mts in the Ice-Age - Romer, Eugeniusz (1871–1954) (["Książnica-Atlas"], 1930)
Skala 1:100 000
1 mapa : kolor. ; 56x69 cm
Mapy poboczne: Dolny Liptów i Przełom Kralowański w skali 1:200 000
Rzeźba terenu przedstawiona za pomocą poziomic i punktów wysokościowych
Czasopismo Geograficzne
Keywords: geomorphological maps; Tatra Mountains

Sezonowa i wieloletnia zmienność niektórych elementów klimatu w Tatrach i Karkonoszach w latach 1951–2015 = Seasonal and multiannual variability of selected elements of climate in the Tatra and Karkonosze Mts over the 1951–2015 period - Błażejczyk, Krzysztof. Autor (IGiPZ PAN, 2019)
Mountain areas are ecosystems very vulnerable to fluctuations and changes of climate. As a consequence, research into climate and climate change in Poland’s Karkonosze and Tatra Mountains has been ongoing for several years now, and has already yielded essential information regarding these highest ranges in Poland. However, there remains a paucity of research comparing features of climate in the two chains of mountains. In consequence, the work detailed here has sought to compare key climate characteristics in these ranges, as well as their seasonal and multiannual changes over the period 1951‒2015. The research is based on daily meteorological records from within the network of Poland’s Institute of Meteorology and Water Management – National Research Institute. In the case of the Karkonosze Mts., it was the meteorological stations at Śnieżka (Ś, 1603 m a.s.l.) and Jelenia Góra (JG, 344 m a.s.l.) that were chosen; while in the Tatras the selected stations were on Kasprowy Wierch (KW, 1990 m a.s.l.) and in Zakopane (Z, 857 m a.s.l.). Additionally, the station at Hala Gąsienicowa (HG, 1520 m a.s.l.) was considered in line with data available for the shorter 1981‒2015 period. The research took account of daily data on air temperature, relative humidity of the air, wind speed, precipitation and snow cover. Specifically, the climate characteristics calculated and analysed by reference to mean multiannual, yearly and seasonal values related to air temperature, maximum temperature, minimum temperature, precipitation totals and maximum snow depth. Further analysis related to numbers of days with precipitation and snow cover, as well as numbers of days with specific air temperatures described as hot (Tmax >25°C), frosty (Tmax <0°C), very frosty (Tmin<-10°C) and icy (Tmax<-10°C). Several climate similarities and differences between the Tatra and Karkonosze Mts. were found to include: 1. mean annual altitudinal gradients for air temperature that are similar for the Tatras (-0.53°C per 100 m) and the Karkonosze (-0.55°C/100 m), 2. the coldest month at the bottoms of both ridges being January, and the warmest July; while top stations feature a 1-month delay, in the sense that February and August are the coldest and warmest months respectively, 3. differing altitudinal gradients of maximum temperature, with the Tatras reporting -0.77°C per 100 m and the Karkonosze – -0. 88°C/100 m, 4. yearly precipitation totals and altitudinal precipitation gradients that are significantly less well-marked in the Karkonosze than in the Tatras (respectively 1212 and 1721 mm, as well as 38.0 and 52.9 mm per 100 m), 5. more precipitation days on Śnieżka than Kasprowy Wierch (237 v 227), 6. relative humidity of air that is highest in autumn and winter below the two ranges, while being highest at the summits in summer, 7. a wind speed in the Karkonosze that is higher than in the Tatras; i.e. 12.2 v 6.6 m/s at the summits, and 2.5 and 1.4 m/s respectively down below, 8. snow cover of 218 days duration at the top of the Tatra Mts., as opposed to 187 days on Mt. Śnieżka. The study also considered multiannual changes in elements of climate over the 1951–2015. Trends achieving statistical significance (with 99, 95% or 90% confidence levels) were confined to just some of the characteristics and stations. Nevertheless, the Tatra and Karkonosze Mts. have experienced an increase in mean annual air temperature – respectively of 0.20–0.27 and 0.22–0.40°C each consecutive 10-year period. Significant changes were also observed for maximum temperature, Tmax equal to 0.35–0.36°C per 10 years in the Tatras and 0.4–0.5°C per decade in the Karkonosze. In the case of precipitation totals the only significant change in value is that noted for Śnieżka top, where the trend is a downward one equal to some 71 mm per 10 years. Where snow cover was concerned, the only effect was a slight decrease in the number of snowy days recorded at Zakopane, located just below the Tatra Mountains
24 cm
Keywords: climate; climate change; Tatra Mountains; Karkonosze Mountains

Zarys historii badań przemarzania gruntu i wieloletniej zmarzliny w polskiej części Tatr = An outline of the history of ground freezing and permafrost research in the Polish Tatra Mountains - Kędzia, Stanisław (IGiPZ PAN, 2015)
24 cm
Keywords: permafrost; ground freezing; Tatra Mountains